PENERAPAN METODE PEMBELAJARAN MIND MAPPING PADA MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SD - Kartika Wulandari; Ismail Marzuki; Nanang Khoirul Umam (Nusantara Hasana Journal, 2025)
This study was motivated by the low learning outcomes of fifth,grade students in science subjects at SD Negeri 83 Gresik, particularly in the theme "Heat and Its Transfer" and the subtheme "The Effect of Heat on Life." One of the contributing factors is the use of conventional teaching methods that fail to actively engage students. Therefore, this research aims to examine the effectiveness of the mind mapping method in improving student learning outcomes. The research employed a Penelitian Tindakan Kelas (PTK) design conducted in one cycle, involving 15 fifth,grade students as research subjects. Data collection techniques included observation of teacher and student activities, learning outcome tests, and documentation. The findings reveal a significant improvement in student learning outcomes following the implementation of the mind mapping method, with the average score increasing from below the Minimum Mastery Criteria (KKM) to an average of 90. Student learning activity also showed a marked increase, with 87% of students participating actively during the learning process. Observations of teacher activities yielded a score of 90%, indicating the teacher's effective classroom management using this method. The study concludes that the use of mind mapping is proven to be effective in enhancing students' learning outcomes and promoting active engagement during science learning. Additionally, this method fosters a more interactive, enjoyable classroom atmosphere and encourages students to think critically and creatively. Hence, the mind mapping method is highly recommended for science instruction as well as other subjects in primary education.